Customer Satisfaction Analysis with Importance Performance Analysis on Academic Services at Faculty of Dentistry, University X - Ajie Ahmad Safar; Endang Chumaidiyah; Ilma Mufidah (Jurnal Rekayasa Sistem & Industri, 2023)
Service is the key to success in various businesses or activities of a services. The success of a service can beseen when the customer receives the service as expected. Based on data at the Faculty of Dentistry UniversityX, student satisfaction score on academic services are still low. The purpose of the study was to determinethe level of student satisfaction and evaluate the attributes of academic services in the Dental ProfessionalEducation program, Faculty of Dentistry, University X. Data was collected using a questionnaire with theService Quality method (SERVQUAL) which consists of 5 dimensions, Reliability, Tangibles, Assurance,Responsiveness, and Empathy. Data processing using SPSS 25, the Customer Satisfaction Index method(CSI) is used to determine the level of student satisfaction with the quality of academic services, ImportancePerformance Analysis method (IPA) is used to determine the attributes of academic services that must bemaintained and improved. The results of this study indicate that the level of student satisfaction withacademic services is 80.23%. The results of the IPA analysis show that there are 2 attributes that must beimproved in quadrant A Assurance dimension, V9 (Ease of reporting work results) and V10 (Ease ofobtaining the information about grades and work progress).